Public Sector Reforms and Anti-Corruption Policies in Nigeria - Braji, Ibrahim (NIU Journal of Social Sciences, 2025)
This study examines how public sector reforms and anti-corruption policies and agencies were implemented and established in Nigeria from colonial times to the present. Using the hybrid theoretical framework that incorporates institutional, principal-agent and social norms theories, the paper closely studies the policies and institutions that different governments used to fight corruption. These include early actions like the Foster-Sutton Tribunal (1956), the Recovery of Public Property Decree, 1984, the establishment of the Code of Conduct Bureau, 1979, the Independent Corrupt Practices and Other Related Offenses Commission, (2000), the Economic and Financial Crimes Commission, (2003) and recent reforms like the Proceeds of Crime (Recovery and Management) Act, (2022) and the Digital Asset Management Systems started by President Tinubu (2024). While these initiatives reflect a consistent policy commitment to transparency and accountability, the study points out ongoing challenges, such as elite impunity, political interference, weak enforcement, lack of institutional continuity, overlapping roles and limited public confidence. Despite some good efforts, Nigeria's fight against corruption has often been weakened by societal norms and structural contradictions. The study concludes by proposing a holistic approach to reform and strengthen anti-corruption agencies to ensure judicial independence and foster a culture of accountability across all the levels of government. This study adds to the broader discourse on governance in Nigeria by offering a theory-based analysis of reform paths and their different results based on political history. Keywords: Corruption, Public Sector Reform, Anti-Corruption Policies and Anti-Corruption Agencies